Enhanced Energy Management Strategy for Standalone Systems Integrating Fuel Cells, Batteries, and Supercapacitors - Mokrani Zahra; Oubelaid Adel; Rekioua Djamila; Rekioua Toufik; Avikal Shwetank; Bajaj Mohit (E3S Web of Conferences, 2024)
Hybrid systems combining fuel cells with battery and supercapacitor storage offer a promising solution for efficient and flexible energy management. Fuel cells, which convert chemical energy into electrical energy, provide a clean and sustainable power source but face challenges like slow response times and limited power density. Integrating batteries and supercapacitors addresses these issues: batteries offer high energy density and stable power supply over longer durations, while supercapacitors deliver rapid bursts of energy and quick charge-discharge cycles. Effective power management in hybrid fuel cell systems is crucial for maximizing efficiency, performance, and lifespan while ensuring reliable energy supply. The hybrid system consists of a PEM fuel cell, batteries, and a supercapacitor (SC) and introduces a power management strategy to ensure the supply of the load.